Spatiotemporally Controlled Plasticity and Elasticity in 3D Multi-Shape Memory Structures Enabled by Elemental Sulfur-Derived Polysulfide Networks with Intrinsic NIR Responsiveness - Lee, Ji Mok; Choi, Yong-Seok; Noh, Guk Yun; Lee, Woohwa; Yoo, Youngjae; Kim, Dong-Gyun; Yoon, Ho Gyu; Kim, Yong Seok (WILEY-V C H VERLAG GMBH, 2020)
Thermadapt shape memory polymers (SMPs), utilizing a variety of dynamic covalent bond exchange mechanisms, have been extensively studied in recent years but it is still challenging to address several constraints in terms of limited accuracy and complexity for constructing 3D shape memory structures. Here, an effective and facile preparation of thermadapt SMPs based on elemental sulfur-derived poly(phenylene polysulfide) networks (PSNs) is presented. These SMPs possess intrinsic near-infrared (NIR)-induced photothermal conversion properties for spatiotemporal control of their plasticity and elasticity. The NIR-controllable plasticity and elasticity of the PSNs enable versatile shape manipulation of 3D multi-shape memory structures, including building block assembly, reconfiguration, shape fixing/recovery, and repair.
Keywords: DYNAMIC COVALENT POLYMERS; INVERSE VULCANIZATION; STIMULI